Imagining technology-enhanced learning with heritage artefacts: teacher-perceived potential of 2D and 3D heritage site visualisations - Lackovic, Natasa; Crook, Charles; Cobb, Sue; Shalloe, Sally; D'Cruz, Mirabelle (Taylor & Francis, 2015)
Background: There is much to be realised in the educational potential of national and world heritage sites. Such sites need to be supported in sharing their resources with a wide and international public, especially within formal education. Two-dimensional (2D) and three-dimensional (3D) heritage site visualisations could serve this need. Our study focuses on the teacher-perceived possibilities and benefits for education around such visualisations. Purpose: We describe how a group of UK teachers perceive the potential of cross-curricular learning that could arise from an Italian world heritage site. The teachers commented on 2D visualisations of artefacts from this site, as well as the design of a 3D immersive environment to serve educational purposes. We consider as follows: (1) how the cross-curricular teaching potential of such resources is perceived, and (2) what design features of a 3D immersive environment teachers suggest are needed for educational explorations. Sample: We recruited 10 teachers from the Midlands region of the UK and carried out semi-structured interviews. Methods: Interviews were transcribed and a thematic analysis applied to the conversations. Questioning was grounded in the examination of 2D and 3D visual resources. This provoked cross-curricular and educational design thinking. Results: Teacher responses highlighted a wide range of cross-curricular possibilities. However, they expressed a more ‘assimilative’ than ‘accommodative’ approach when relating resources to the curriculum. Such ‘assimilation’ involved seeing the site artefacts as raw material for more instrumental ‘curriculum activities’ (e.g. within art and design, geography, maths or literacy) rather than a more accommodative approach whereby curricular disciplines were exercised to make new meaning from the artefacts. In relation to 3D technology design, most teachers highlighted three technology features that would render it well matched to educational practice and three educational benefits over non-3D immersive environments. Conclusions: Teachers can easily imagine a rich range of opportunities to utilise 2D and 3D heritage site artefacts within the curriculum. However, the largely assimilative nature of this cross-curricular appropriation suggests the value of providing more guidance and support to teachers in the interpretation and application of artefacts. Their design suggestions can usefully inform construction of educational features within 3D immersive technologies that support heritage site experiences.